Neuroleadership as a Tool for Combating Unethical Behaviour in the South African Public Sector: Addressing Historical Trauma and Leaders - Nhari, Sibongile R; Nzimakwe, Thokozani I. (JEBIM Prima, 2025)
This paper is a narrative review exploring how an understanding of how brain function underlying leadership behaviour and decision making -neuroleadership- can be utilised to address unethical behaviour, including nepotism, corruption and fraud, in the South African public sector, aggravated by various circumstances, one of which is historical trauma from the apartheid era. Notwithstanding countless legislative efforts to curb unethical practices, South Africa continues to experience widespread corruption in its public sector, particularly within municipalities. We suggest unresolved historical trauma as further fuelling unethical practices among leaders who feel disadvantaged by previous political systems. This paper investigates how neuroleadership principles, including self-awareness, emotional regulation and social cognition have the potential to address these behaviours. The findings are that neuroleadership offers a novel strategy for studying and teaching ethical leadership in the South African public sector by enhancing among others, emotional regulation and bias awareness, with the potential to address the severe challenges municipalities face, such as financial mismanagement, and procurement irregularities. Integrating neuroleadership into ethics training programs for public officials is recommended to promote emotional intelligence and cognitive flexibility, while addressing underlying historical traumas is suggested to help mitigate unethical behaviour and foster more inclusive leadership practices.